FEATURES OF PROCALCITONIN AND C-REACTIVE PROTEIN IN PROLONGED NEONATAL HYPERBILIRUBINEMIA. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents the causal mechanisms of long-term neonatal hyperbilirubinemia. Modern methods of studying inflammatory markers are described. Early signs of inflammatory activity in chronic hyperbilirubinemia of rats.